Sex, Blasphemy, and the Block: The Trial and Execution of Ludwig Hätzer - Dipple, Geoffrey (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2017)
In early 1529, the Protestant authorities of Constance executed Ludwig Hätzer for disobedience and moral depravity. Although the court documents avoided any reference to his religious teachings, contemporaries speculated about the role that perceptions—that he was an Anabaptist who espoused heretical opinions—played in his conviction. This article uses Hätzer’s trial and execution as an opportunity to reflect on two topics of interest in studies of the early Reformation: the reluctance of reformers to level charges of heresy against each other, and their re-evaluation of human sexuality resulting from the rejection of clerical celibacy.